AKTIVITAS ANTIHIPERURISEMIA KOMBINASI EKSTRAK DAUN KERSEN (MUNTINGIA CALABURA L.) DAN DAUN SIRSAK (ANNONA MURICATA L.) TERHADAP TIKUS PUTIH JANTAN: ANTIHYPERURICEMIA ACTIVITY OF EXTRACT COMBINATION OF KERSEN LEAF (MUNTINGIA CALABURA L.) AND SOURSOP LEAF (ANNONA MURICATA L.) ON MALE WHITE RATS - Susanti, Laila; Samsuar; Ariawan, M Wahyu; Widiyastuti, Asih; Isbiyantoro; Widodo, Subur (JFL : Jurnal Farmasi Lampung, 2024)
Kersen (Muntingia calabura L.) and soursop (Annona muricata L.) have many properties to cure several diseases, including antihiperurisemia, which is a disorder of purine metabolism in which patients experience increased uric acid levels. This study aimed to examine the antihiperuricemia effect of a combination of kersen leaf extract and soursop in male rats orally. Extraction was carried out by maceration using 70% ethanol. This research is a laboratory experimental study using male white mice as test animals. Data were processed in the form of ANOVA and LSD (Least Significant Difference) test results to compare between groups P0 (normal control), PI (negative control), P2 (Allopurinol 9 mg/Kg BW), P3 (410 and 3.5 mg/Kg BW), P4 (410 and 7 mg/Kg BW), P5 (410 and 10.5 mg/Kg BW), P6 (610 and 3.5 mg/Kg BW), P7 (610 and 7 mg/Kg BW), P8 (610 and 10.5 mg/Kg BW), P9 (910 and 3.5 mg/Kg BW), P10 (910 and 7 mg/Kg BW) ), P11 (910 and 10.5 mg/Kg BW). Giving the test material starting on the 8th to 14th day. On the 15th day blood was taken by slaughtering to measure uric acid levels using a UV-Vis spectrophotometer. On examination of uric acid levels, the administration of beef liver can significantly increase uric acid levels in male rats. and the administration of kersen leaf extract and soursop leaves can significantly reduce uric acid levels in male rats. The administration of kersen leaf extract and soursop leaves for 7 days at doses of 910 and 10.5 mg/Kg BW most effectively reduced uric acid levels in hyperuricemic mice.   Keywords: Hyperuricemia, kersen leaves extract, soursop leaves extract